PETANI DITENGAH TAMBANG :Studi Fenomenologi EfekImplementasi Kebijakan Terhadap Kehidupan Petani di Morowali - Eymal B. Demmallino; Tamzil Ibrahim; Abdurrahman Karim (Jurnal Sosial Ekonomi Pertanian, 2018)
The life of a farmer is very different due to the implementation of the mining policy. The purposes of this research were to know the actual condition of the community life of farmers in the ring area of the mine in District of Bahodopi and to analyze the impact of nickel mining and recommending policy management systems of natural resources that benefit the community of farmers. This approach used a descriptive qualitative approach by observation method with participation, in depth interviews, and documentation. For the data analysis stage of this research, namely data collection by specifying the informant throughpurposive sampling and continued with the reduction of the data by the method of presentation of data, and then snowball and the withdrawal of the conclusion. The results showed nickel mining has positive and negative impacts such as providing employment opportunities and business opportunities; food stalls, souvenir supplies business and housing, the conflict between farmers and companies that are triggered by a mudflow that cascaded into the farmland residents resulting in agricultural output that shrank, the majority of agricultural land is converted into mining areas so that the resulting loss of land as a sourceof intergenerational life, mining does not guarantee social welfare economic community of farmers. For farmers the presence of mine was certain will make an impact long term disaster. The Government should evaluate or review the return policy that has been applied as well as the effects of the current mining management, especially in matters related to agriculture or farmer's life.Keywords: farmers; policy; the response; meaning.